Regarding the political power of the declaration of February 16, 1918 - Laurinavičius, Česlovas (Politologija, 1998)
In this article, the genesis and development of an independent Lithuania-state is being discussed not only on the basis of the traditional methods of historical science, but also in respect to both geopolitical and politological points of view. Such an attempt is not new. At his time, Stasys Šalkauskis tried to solve the problem of Lithuanian self-dependence in a similar way, as if he was seeking an extension in the volume of reflection. (The article by Stasys Šalkauskis titled "Lithuania's Geopolitical State and the Problem of the Lithuanian Culture" is meant here; it was published in "Židinys," spring issue, 1938). Heretofore, at that time the maximum retrospect reserve embraced and limited itself to 20 years. Nowadays, it seems reasonable to discuss the problem of the independent Lithuania-state, although, in a retrospect of 80 years.At a time when Lithuania's Liberation Movement receded from the unionist (universal) traditions and the ethnocentric character was acquired, the process, which was commencing an ambivalent perspective, started. It was aimed at proving victorious not only over the domination of Polonism in the territories of LGD (Lithuanian Grand Dukedom), but also at conveying a sum of preconditions for Russia, eventually - Germany, to superintend over these territories. At the end of the Great World War I, the aforementioned process had reached the stage when the material preconditions concerning the independent Lithuania-state emerged - to compose itself as a balance between Poland, Germany, and Russia. This stage was formally delineated in the Declaration of February 16, 1918. It had elevated the principle to civil self-determination (or according to S. Šalkauskis "the synthesis of cultures") of the whole Lithuanian population. Yet, the movement toward ethnocentrism did not halt, and Lithuania, on its way to independence, had to go through the tragic years of Pangermanism and Panslavism domination. Therefore, no sooner than the end of the XXth century did Lithuania have its independence restored in the new geopolitical circumstances. Furthermore, it seems that the principles established in the Declaration of February 16, 1918, have not lost their power.
Keywords: -